P, Metode studi literatur Pengembangan Media Belajar Digital Aplikasi Kahoot Terhadap Literasi Membaca Siswa Sekolah Dasar: Pendahuluan, Metode Penelitian, Hasil dan Pembahasan. - Alfitriana Purba; Cheisya Anastasya; Fadhillah Sekarsari; Amelya Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to explain how to develop digital learning media using the Kahoot application to improve students' reading literacy skills at the elementary school level. The analysis was conducted using a literature study method, which reviewed various scientific articles from Google Scholar related to the use of Kahoot at various levels of education. The results of the study indicate that the use of Kahoot as a game-based learning tool can increase student participation, motivation, and engagement in reading activities, as well as facilitate interactive broadcasting of reading materials, which has a positive impact on students' understanding and retention of the texts read. On the other hand, the automatic assessment feature in Kahoot makes it easier for teachers to assess learning outcomes and identify literacy problems faced by students more quickly and effectively, despite obstacles such as limited devices, internet access, and device usage policies at school. Overall, the results of the study indicate that Kahoot has great potential as a relevant digital learning medium in supporting the development of reading literacy in elementary schools in the 21st century education era.